Evaluation of an automatic image-based screening technique for neonatal hyperbilirubinemia - Rong, Z H (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2016)
OBJECTIVE: To verify the accuracy of a smart phone software application, which is an automated image-based bilirubin (AIB) testing technique for testing peripheral blood total bilirubin (TB) in term and late preterm neonates